Perception of satisfaction with body image in adolescents from Paredes Secondary School - Flores, Pedro Miguel (2022)
Body image is part of the mechanism of personal identity that can be given as a mental representation of the body itself, reflecting the way individuals think, feel, and behaves in relation to their physical appearance. The perception of an individual’s body image changes due to intrinsic and extrinsic factors and, in adolescence, due to the formation of their identity, the influence of social media and network can be very determinant in their body image perception that have beauty and aesthetics standards difficult to achieve. Sports physical activity (SPA) proves to be a way to maintain or achieve the ideal physical shape, thus it increases the body satisfaction and the perception of body image (PSIC). The main objective of the current study is to evaluate the relationship between the practice of AFD and PSIC in adolescence, Paredes high school. It was concluded that the perception and satisfaction of body image varied according to the practice of physical sports activity in male students. In females, the practice of sports physical activity did not influence the perception and satisfaction of their body image.